POLA ASUH ORANG TUA DALAM PROSES PEMBELAJARAN ANAK DI SEKOLAH - Lydia Selviani; Rina Oktaviana (Jurnal Abdimas Bina Bangsa, 2023)
In adapting to both age and maturity, the family is the first environment that demands. In the family, parents have a big role in the social development of children. Every parent certainly has different parenting styles, including: authoritarian parenting, democratic parenting, permissive parenting. Parenting styles in early childhood include physical, mental, emotional, moral, and social stimulation that will encourage optimal child growth and development. The parenting style of their children will affect the social development and personality of the child. Bad parenting styles will reduce the good social development of children. Parenting style means the norms of parents, fathers and mothers in leading, nurturing, guiding children. Nurturing means taking care of using ways of caring for and educating them. Guiding using how to shape, train, and so on. The quality and intensity of parenting varies in influencing behavior and directing children. Because of this, this article will discuss matters related to parenting in the process of learning children in schools at the Madrasah Al-Aqidah Foundation, Kutapandan Village, Lempuing District, Ogan Komering Ilir Regency, such as the definition of parenting styles, types of parenting styles. . The purpose of this article is to create and enhance understanding of parenting styles for children's learning process at school, thus creating a dream to find or enhance the implementation of parenting styles for the emotional development of children's development at school from an early age for parents